EFEKTIVITAS ANTARA BUAH STROBERI DENGAN BUAH JERUK LEMON SEBAGAI BAHAN ALAMI PEMUTIH GIGI (SECARA IN VITRO) - Titian Gian Yunita; Wiworo Haryani; Sutrisno Sutrisno (Journal of Oral Health Care, 2017)
The color change that occurs teeth often creates an aesthetic issue that greatly affects the appearance, especially for professions that demand excellent performances, such as host, model or actress. Seeing the higher needs and interests of teeth whitening treatment and patients who are sensitive to bleaching materials and the costs to be incurred for this treatment, the authors wanted to provide other alternative. This research was located in preclinical Department of Dental Nursing Poltekkes Yogyakarta in October 2016. The purpose of this study to determine the differences in effectiveness between Strawberry with Lemon as a natural ingredient of tooth whitening. This type of research is an experimental research. This study in vitro using 30 tooth Premolar maxilla and mandible post extraction were divided into 3 groups. Group 1 smeared of strawberry pastes, pasta smeared groups of 2 lemons and group 3 (control) spread with carbamide peroxide 10%. Samples were soaked in coffee for 12 days, then smeared the appropriate group for 15 minutes, 30 minutes and 45 minutes. The color change was observed using Shade guide. Based on the Kruskal Wallis test there is no difference in the average value of the observation are significant (p>0,05) and continued with different test further LSD is by Post Hoc Test obtained difference the color of teeth in the group pasta strawberry and control groups were significant (p<0,05) after 45 minutes basting. Pasta strawberry more effectively than pasta lemons and Carbamide Perokside 10% after 45 minutes basting.